Associations Between White Matter Hyperintensity Burden, Cerebral Blood Flow and Transit Time in Small Vessel Disease: An Updated Meta-Analysis - Stewart, Catriona R.; Stringer, Michael S.; Shi, Yulu; Thrippleton, Michael J.; Wardlaw, Joanna M. (Frontiers in Neurology, 2021)
Cerebral small vessel disease (SVD) is a major contributor to stroke and dementia, characterised by white matter hyperintensities (WMH) on neuroimaging. WMH are associated with reduced cerebral blood flow (CBF) cross-sectionally, though longitudinal associations remain unclear. We updated a 2016 systematic review, identifying 30 new studies, 27 cross-sectional (n=2956) and 3 longitudinal (n=440). Cross-sectionally, 10/27 new studies (n=1019) included sufficient data for meta-analysis, which we meta-analysed with 24 previously reported studies (n=1161), total 34 (n=2180). Our meta-analysis showed that patients with lower CBF had worse WMH burden (mean global CBF: standardized mean difference (SMD): -0.45, 95% confidence interval (CI): -0.64,-0.27). Longitudinally, associations between baseline CBF and WMH progression varied: the largest study (5 years, n=252) found no associations, while another small study (4.5 years, n=52) found that low CBF in the periventricular WMH penumbra predicted WMH progression. We could not meta-analyse longitudinal studies due to different statistical and methodological approaches. We found that CBF was lower in WMH than in normal-appearing white matter in an additional meta-analysis (5 cross-sectional studies; n=295; SMD: -1.51, 95% CI: -1.94,-1.07). These findings highlight that relationships between resting CBF and WMH are complex. Further longitudinal studies analysing regional CBF and subsequent WMH change are required to determine the role of CBF in SVD progression.